Os sentidos da promoção da saúde na atenção básica: estudos de caso na Estratégia Saúde da Família em Belo Horizonte - Monica Soares da Fonseca Beato (2006)
The purpose of this study is to discuss the social construction of meanings about health promotion, in a specific context which is the Family Health Strategy in Sistema Único de Saúde (The Public Health System). Having as an aim the integral attention, this new perspective of performance proposed by the World Health Organization is still anchored in other principles that overcome the strict biomedical perspective, such as intersetoriality, social networks, social participation and empowerment. Despite it is frequently interpreted as a proposition over any epistemological critique, the promotion of health shows multiple senses and may cause semantic and ideological glides in real intervention actions, mainly in what is concerned the concepts of risk, autonomy and community. Because of that, this study was developed under Michel Foucaults discursive perspective, when looking into the health promotion area as a social disputed object which may take different ways when it becomes a strategy action. The essence of the object is not searched, but it is intended to transit from the micro-processes of meaning production to the conceptual and institutional issues, always related to the power and the knowledge which are present in the daily relationships. The French Discourse Analysis is an auxiliary theoretical-methodological instrument. In relation to the field research, the guidelines of the strategy in Belo Horizonte are brought to discussion, having as sources an interview with the director and a documentary research. In another moment closer to the routine of the actions of basic attention, the discursive practices of two Health Family groups are analysed. Semi-structured interviews were made with those professionals, besides active observation. Although having studied in the discursive field a predominance of actions for preventing illnesses with a strong calling to the change of habits, there are other discourses that are not connected to this discourse formation. The nutrition project of the first group and the mental health project from the second one are some examples. However, what is more highlighted is the frequent polarization between the clinic and the pragmatic collective actions, both based on a logic which is rarely in touch with each other, overlapping in only one Strategy for Ministry rules. We discuss some reasons why the problematization of experiences, the understanding of the territory and initiatives of the local existing knowledge are rare.